Experimental Investigation on Thermophysical and Stability Properties of TiO2/Virgin Coconut Oil Nanofluid - Barlin Oemar; Amir Arifin; David Bahrin; Astuti; Dwiki Ramadhan; Muhammad Abil Rifqy; Muhammad Reza Tinambunan (Science and Technology Indonesia, 2023)
This paper shows experimental study results on the thermophysical and stability of nanofluids of Titanium oxide (TiO2) dispersed in high-purity of Virgin Coconut Oil (VCO). Nanofluid samples that functioned as a lubricant were prepared by a two-step preparation method at different volume fractions (0.1, 0.3, and 0.5 vol.%) and different temperatures (28, 40, and 100°C). The dynamic viscosity and density were performed using Falling Ball Viscometer and Pycnometer, respectively. The sedimentation photograph method using a digital camera was applied to analyze the stability. A maximum dynamic viscosity enhancement of 62.78% was recorded for TiO2/VCO nanofluid with 0.5% nanoparticle volume fraction and at the temperature of 100°C). Whereas, the highest density improvement was recorded for TiO2/VCO nanofluid with 0.5% nanoparticle volume fraction. Freshly prepared nanofluids did not show any significant change in stability. However, a trivial phase separation appeared in the samples after 8 days. The results indicated that adding TiO2 nanoparticles increased the dynamic viscosity and density. It can be concluded that the volume in fraction has the effect to enhance the thermophysical stability of TiO2/VCO nanofluids.